Efficiency of RNA Interference in the Mouse Hematopoietic System Varies between Cell Types and Developmental Stages - Oberdoerffer, Philipp (American Society for Microbiology, 2005)
RNA interference (RNAi) is a naturally occurring posttranscriptional gene-silencing mechanism that has been adapted as a genetic tool for loss-of-function studies of a variety of organisms. It is more widely applicable than classical gene targeting and allows for the simultaneous inactivation of several homologous genes with a single transgene. Recently, RNAi has been used for conditional and conventional gene inactivation in mice. Unlike gene targeting, RNAi is a dynamic process, and its efficiency may vary both between cell types and throughout development. Here we demonstrate that RNAi can be used to target three separately encoded isoforms of the bcl-2 family gene bfl-1/A1 in a conditional manner in mice. The extent of gene inactivation varies between different cell types and is least efficient in mature lymphocytes. Our data suggest that RNAi is affected by factors beyond small interfering RNA-mRNA stoichiometry.